Dùng phương pháp cộng hưởng từ hạt nhân (NMR) để xác định độ axit, phân bố nhôm trong vật liệu ZSM-5 và ZSM-5/MCM-41 - Hoài Nam và cộng sự, Lê Thị (Vietnam Journal of Chemistry, 2014)
ZSM-5/MCM-41 composite was prepared by using a dual-template synthetic gel system - Tetrapropylamoniumhydroxit TPAOH and cetyltrimetylamoniumbromide CTMAB. The structure of that material was investigated by IR, XRD, TEM, and TPD-NH3 and nitrogen adsorption/desorption [1]. The results of IR, XRD, NMR showed that the most of aluminum atoms distributed in the framework In this paper, 27Al, 1H MAS NMR are used to determine the geometry of the Bronsted acid and the distribution of aluminum atoms in ZSM-5/MCM-41. Acidic (“bridging”) OH groups in ZSM-5/MCM-41 are responsible for the catalytic activity. They can exist in materials in four forms: SiOHAl (d = 4.1 ppm), AlOH (d = 2.7ppm), SiOH1 (d = 1.8 ppm), and SiOH2 (d = 2.2 ppm). Here, we can see the differences of acidities between ZSM-5 and ZSM5-/MCM-41 base on the signals of the formation of bridging OH groups (SiOHAl).